Influence of Metal Catalyst on SnO2 Nanowires Growth and Gas Sensing Performance - Dario Zappa; Rebecca Melloni; Valentin-Adrian Maraloiu; Nicola Poli; Marco Rizzoni; Veronica Sberveglieri; Orhan Sisman; Matteo Soprani; Elisabetta Comini (Proceedings, 2017)
In the present work SnO2 nanowires were synthetized by using vapour-liquid-solid technique (VLS) on alumina substrates, using different metal nanoparticles as catalyst for the growth. In particular, the effect of Au, Sn and Pd nanoparticles was exploited. The growth was performed simultaneously on all substrates, keeping the same conditions for the three different catalysts used. Nanowires were investigated by FE-SEM, HR-TEM, and XRD measurements, confirming the morphology and the crystalline structure of the material. Moreover, conductometric sensing devices were fabricated depositing electrodes on top of these materials, and chemical sensing performances were evaluated toward some typical air pollutants.